Lipase-catalysed polycondensation of levulinic acid derived diol-diamide monomers: access to new poly(ester-co-amide)s. Issue 47 (12th November 2020) - Meimoun, Julie; Bernhard, Yann; Pelinski, Lydie; Bousquet, Till; Pellegrini, Sylvain; Raquez, Jean-Marie; De Winter, Julien; Gerbaux, Pascal; Cazaux, Frédéric; Tahon, Jean-François; Gaucher, Valérie; Chenal, Thomas; et al.
Abstract : A new family of biobased poly(ester- co -amide)s is reported from the enzymatic polycondensation of a library of levulinic acid derived diol-diamide monomers with diesters. Abstract : Research toward bio-based polymers is an expanding field due to environmental concerns. A library of new aliphatic diol-diamide monomers with different chain lengths between the two amido groups was synthesized from sustainable levulinic acid and various linear aliphatic diamines (C2 –C10 ). The monomers were prepared by diacylation of the diamines followed by reduction of the ketones to alcohols. These secondary diols were successfully recognized by an enzyme and polymerised in solution through a lipase-catalysed polycondensation. Poly(ester- co -amide)s with number-average molecular weights ( M n ) in the range of 1300–7200 g mol −1 were obtained, with dispersities between 1.5 and 1.8. An improvement of the M n value was observed upon increasing the monomer chain length. The variation of the aliphatic diol allows modulating the thermal properties of the final polymers. The glass transition temperatures were found to be between −23 °C and 0 °C. The polymers containing a long aliphatic segment (C8 –C10 ) were able to crystallize (melting temperature of 90–97 °C). TGA analyses showed that the ester linkages degrade at lower temperatures than the amide bonds. The stability of the latter was found to be higher when the number of methylene units increased from 2 (355 °C) to 10 (378 °C). This kind of biopolymer could be used as a drug delivery system or for tissue engineering applications.